Establishment of cell-lines stably expressing recombinant Japanese eel follicle-stimulating hormone and luteinizing hormone using CHO-DG44 cells: fully induced ovarian development at different modes - Kazeto, Yukinori; Ito, Risa; Tanaka, Toshiomi; Suzuki, Hiroshi; Ozaki, Yuichi; Okuzawa, Koichi; Gen, Koichiro (Frontiers in Endocrinology, 2023)
Abstract The gonadotropins (Gth), follicle-stimulating hormone (Fsh) and luteinizing hormone (Lh), play central roles in gametogenesis in vertebrates. However, available information on their differential actions in teleost, especially in vivo, is insufficient. In this study, we established stable CHO-DG44 cell lines expressing long-lasting recombinant Japanese eel Fsh and Lh with extra O-glycosylation sites (Fsh-hCTP and Lh-hCTP), which were produced in abundance. Immature female eels received weekly intraperitoneal injections of Gths. Fsh-hCTP induced the entire ovarian development by 8 weeks from the beginning of injection; thus, the ovaries of most fish were at the migratory nucleus stage while the same stage was observed in eels after 4 weeks in the Lh-hCTP-treated group. In contrast, all pretreated and saline-injected eels were in the pre-vitellogenic stage. Gonadosomatic indices in the Fsh-hCTP-treated group were significantly higher than those in the Lh-hCTP group at the migratory nucleus stage because of the significantly higher frequency of advanced ovarian follicles. Ovarian mRNA levels of genes related to E2 production (cyp11a1, cyp17a1, cyp19a1, hsd3b, fshr, and lhr) were measured using real-time quantitative reverse transcription-polymerase chain reaction (RT-PCR). All genes were induced by both Fsh-hCTP and Lh-hCTP, with a peak at either the mid- or late vitellogenic stages. Transcript abundance of cyp19a1 and fshr in the Lh-hCTP group were significantly higher than those in the Fsh-hCTP group, whereas no difference in the expression of other genes was observed between the groups. Fluctuations in serum levels of sex steroid hormones (estradiol-17, 11-ketotestosterone, and testosterone) in female eels were comparable in the Fsh-hCTP and Lh-hCTP groups, thus increasing toward the maturational phase. Furthermore, the fecundity of the eels induced to mature by Fsh-hCTP was significantly higher than that induced by Lh-hCTP. These findings indicate that Fsh and Lh can induce ovarian development in distinctively different modes in the Japanese eel.